Synthesis, structure and properties of N-alkoxy-N-(1-pyridinium)urea salts, N-alkoxy-N-acyloxyureas and N,N-dialkoxyureas - Shtamburg, V. G.; Shishkin, O. V.; Zubatyuk, R. I.; Kravchenko, S. V.; Tsygankov, A. V.; Shtamburg, V. V.; Distanov, V. B.; Kostyanovsky, R. G. (Elsevier Inc., 2007)
N-Alkoxy-N-(1-pyridinium)urea salts 3, 4 have been prepared, the conversions of N-acetoxy-N-methoxyurea 7 into N,N-dimethoxyurea 8 and of N-n-propyloxy-N-(1-pyridinium)-N',N'-dimethylurea chloride 6 into N,N dimethoxy-N',N'-dimethylurea 11 were carried out. A high pyramidality of the amide nitrogen in O–N–X groups [X = N+C5H5, OMe, OC(O)C6H4Cl-p] has been revealed by XRD studies of ureas 3b, 8 and N-p chlorobenzoyloxy-N-n-butyloxyurea 9.